Comparison of extractive content between sapwood and heartwood of timber species ara - Abdul Razak, Mohd Badrul Hisham (2002)
Ara or tree with scientific name Ficus is a one of the large genus with about 600 species in all the warmer part in of the earth. The biggest is in tropical region and mainly in Indo - Malaysians. There are about 101 species in Malaya (second largest genus of plants after Eugenia). The characteristics of Ara (Ficus) are having a grain interlocked, coarse texture and a timber of soft to moderately hard in natuer. The sapwood and heartwood is not differentiated, light yellow to various shades from yellow to pinkish grey and the durability variable in resistant to insect attack and decay. At present this timber Ara is not commercial use, but more commonly found as an ornamental plant because of its deep green leave and long red stipules. There are many species of Ficus like Ficus Mikrocarpa, Ficus Roxburghii, Ficus Religiosa and Ficus Elastica (planted in Malaya on a large scale for tapping India rubber before the advent of para - rubber). The characteristic of Ara is the trees, shrubs woody epiphytic climber and stranglers or woody creepers with latex. The bark of Ara is generally pale grey and smooth.